2014
DOI: 10.1055/s-0034-1390739
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for large superficial colorectal tumors using the “clip-flap method”

Abstract: The clip-flap method is a simple, safe, and effective option for ESD of large superficial colorectal tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 12 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…Clip flap is simple and effective, but it is an indirect traction method which strengthens the traction force by gravity. Thus, it does not always provide sufficient traction . To overcome these problems, we modified the “clip‐with‐line” method and developed TAC‐ESD, which does not require withdrawal of the colonoscope.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clip flap is simple and effective, but it is an indirect traction method which strengthens the traction force by gravity. Thus, it does not always provide sufficient traction . To overcome these problems, we modified the “clip‐with‐line” method and developed TAC‐ESD, which does not require withdrawal of the colonoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it does not always provide sufficient traction. 26 To overcome these problems, we modified the "clip-with-line" method [27][28][29][30][31] and developed TAC-ESD, which does not require withdrawal of the colonoscope. However, TAC-ESD has a weak point.…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, we showed the case of successful traction‐assisted ESD using dental floss and a clip for a huge SNADET in which severe fibrosis of the submucosal layer was expected due to repeated biopsies. Traction‐assisted ESD methods include thread and clip traction, S‐O clip, ring‐shaped thread traction, clip‐flap method, and clip‐and‐snare method . For ESD of lesions in the esophagus, stomach, and colorectum, the most appropriate method is selected by considering several factors, such as the space within the hollow organ where the lesion is located and the need for removing the scope while applying traction.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that risk factors for incomplete resection or perforation in colorectal ESD are poor operability of the scope, submucosal deep invasion, or severe fibrosis [10,11]. Several traction methods can be used to maintain the field of view [12][13][14][15][16][17][18][19][20][21][22]. However, with conventional traction methods, it is difficult to control the direction and intensity of traction or a combination of special equipment may be required.…”
Section: Introductionmentioning
confidence: 99%